The global procurement landscape of leishmaniasis medicines. - Hye Lynn Choi; Saurabh Jain; José A Ruiz Postigo; Bettina Borisch; Daniel Argaw Dagne (PLoS Neglected Tropical Diseases)
Ensuring access to essential medicines for leishmaniasis control is challenging, as leishmaniasis is a very small and unattractive market for pharmaceutical industry. Furthermore, control programmes are severely underfunded. We conducted an analysis of global procurement of leishmaniasis medicines for the past 5 years in order to shed light on the current leishmaniasis market landscape and supply and demand dynamics. We estimated global demand of each leishmaniasis medicines, the amount of each medicine required to treat all reported cases, based on the number of cases reported to WHO and the first-line treatment regimen used in each country. Procurement data were obtained from procurement agencies, international organizations, WHO, national leishmaniasis programmes and manufacturers. Expert interviews were conducted to have a better understanding of how medicines were procured and used. The comparison of estimated need and procurement data indicated discrepancies in supply and demand at global level as well as in the most endemic countries. The extent of the gap in supply was up to 80% of the needs for one of the leishmaniasis medicines. Mismatch between supply and demand was much wider for cutaneous leishmaniasis than visceral leishmaniasis. This study presents a current picture of procurement patterns and imbalance in global supply and demand. Addressing improved access and supply barriers requires concerted and coordinated efforts at the global and national levels. Priority actions include setting up a procurement coordination mechanism among major procurers, partners and national programmes where forecasting and supply planning is jointly developed and communicated with manufacturers. In addition, continuous engagement of manufacturers and advocacy is critical to diversify the supplier base and ensure quality-assured and affordable generic medicines for leishmaniasis.